Structural Evolution of Ferroelectric and Ferroelastic Barium Sodium Niobate Tungsten Bronze - Aamlid, Solveig Stubmo (Inorg Chem, 2020)
[Image: see text] The crystal structure of the ferroelastic and ferroelectric tungsten bronze Ba(2)NaNb(5)O(15) (BNN) has been debated. Here, we re-examine the crystal structure of BNN by ambient powder X-ray diffraction combined with density functional theory calculations. We demonstrate that the room temperature space group is Cmm2 with significant cation disorder on the Ba and Na cation sublattices. Density functional theory calculations reveal a relatively flat energy landscape between structures of different symmetries, including the energetics of cation disorder. We also study the structural evolution and the ferroelectric and ferroelastic phase transitions by high-temperature X-ray diffraction and dilatometry. The ferroelectric phase transition at 570 °C is of first order and cause the cell to expand in the c direction, while the ferroelastic distortion starting at 270 °C takes place in the ab plane and does not affect the polarization. The phase transitions are not coupled, which means that BNN is a ferroic material with two primary and uncoupled order parameters.